IMPROVE SCIENTIFIC ABILITIES STUDENTS THROUGH MODEL DEVELOPMENT TESTING EXPERIMENTS - Basid, Abdul; Rusli, Rusli (Jurnal Neutrino, 2018)
A Study on the development of an Testing Experiments model has been carried out which aims to improve the scientific abilities of students in the Physics Department. This study is motivated by the implementation of practicum that has almost no innovation, no change, always verifying patterned and less developing students' science process skills. The 4-D model RD approach was used to develop this practicum model. The instrument used is a handout that is equipped with a rubric as a practical guide and assessment guide. A total of 20 students were involved as research subjects. The results showed in general there was an increase in student scientific abilities. Of all the sub-abilities developed, the average percentage of achievement scores reached 60% in almost all sub-abilities after the 4th or 5th practicum or at the fourth or fifth week. However, there are sub-skills already reaching 60% in the 3rd practicum. Student and peer responses show that this practical model is better and more comprehensive in developing students' scientific abilities.